ELECTRONIC PROCUREMENT OF GOVERNMENT GOODS/SERVICES (E-PROCUREMENT) FROM THE PERSPECTIVE OF COLLABORATIVE GOVERNANCE IN THE CITY OF PEKANBARU - Monica Patricia Br. Simanjuntak; Zaili Rusli (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study discusses the implementation of Government Goods/Services Procurement Electronically (E-Procurement) from the perspective of Collaborative Governance in Pekanbaru City. The focus of this research is on the effetiveness of e-catalogs, the involvement of local business actors, and cooperation between local government agencies. The aim of this research is to analyze and describe the e-procurement process within a collaborative framework and to identify the obstacles faced. This research uses a descriptive qualitative approach with data collection techinuques through interviews with the local UKPBJ of Pekanbaru City, the Departement of Trade and Industry of Pekanbaru City, the Inspectorate of Pekanbaru dan the Department of Cooperatives and MSMEs of Pekanbaru City. The result of this study indicate that collaboration among actors is on going but not yet optimal, especially in horizontal dimensions. The involvement of local business actors is still limited due to a lack of technical assistance and information. This research recommends strebgthening the role of local governments as facilitators of collaboration, enchancing the capatity of business actors, and fostering synergy between institutions to achieve participatory, transparent procurement using domestic products.